America's exhausted paradigm: Macroeconomic causes of the financial crisis and great recession - Thomas I. Palley (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2009)
This paper traces the roots of the current financial crisis to a faulty U.S. macroeconomic paradigm. One flaw in this paradigm was the neo-liberal growth model adopted after 1980 that relied on debt and asset price inflation to drive demand in place of wage growth. A second flaw was the model of U.S. engagement with the global economy that created a triple economic hemorrhage of spending on imports, manufacturing job losses, and off-shoring of investment. Financial deregulation and financial excess are important parts of the story, but they are not the ultimate cause of the crisis. These developments contributed significantly to the housing bubble but they were a necessary part of the neoliberal model, their function being to fuel demand growth by making ever larger amounts of credit easily available. As the neoliberal model slowly cannibalized itself by undermining income distribution and accumulating debt, the economy needed larger speculative bubbles to grow. The flawed model of global engagement accelerated the cannibalization process, thereby creating need for a huge bubble that only housing could provide. However, when that bubble burst it pulled down the entire economy because of the bubble's massive dependence on debt. The old post-World War II growth model based on rising middle-class incomes has been dismantled, while the new neoliberal growth model has imploded. The United States needs a new economic paradigm and a new growth model, but as yet this challenge has received little attention from policymakers or economists.
Keywords: 330